Twinning-mediated work hardening and texture evolution in CrCoFeMnNi high entropy alloys at cryogenic temperature. (5th October 2017) - Liu, T.K.; Wu, Z.; Stoica, A.D.; Xie, Q.; Wu, W.; Gao, Y.F.; Bei, H.; An, K.
Highlights: The slipping twining activities were presented during cryogenic plastic deformation. Deformation twins led to a steady work hardening. Twinning mediated texture evolution was characterized by neutron diffraction. Deformation twinning contributed to the {115}〈552〉 texture component. The microstructure-texture evolution was correlated to mechanical behaviors. Graphical abstract: Abstract: The cryogenic plastic deformation of CrCoFeMnNi high entropy alloy is characterized by three distinct stages based on the change of the work hardening rate. Microstructure and bulk texture at different strain levels were studied by electron backscatter diffraction (EBSD) and neutron diffraction. Our findings indicate that the deformation twins led to the constant work hardening rate at Stage II and resulted in the appearance of 〈115〉//TA texture component, while the dislocation slip was involved all though the entire plastic deformation. The twinning-mediated tensile plastic deformation at cryogenic temperature finally induced the strong {111}-〈112〉 texture component and minor {001}〈110〉 texture component accompanied with twinning-induced {115}〈552〉 texture component.